EGFR-targeting polydopamine nanoparticles co-loaded with 5-fluorouracil, irinotecan, and leucovorin to potentially enhance metastatic colorectal cancer therapy - Rania Djermane; Celia Nieto; Milena A. Vega; Eva M. Martín del Valle (Scientific Reports)
Abstract Despite all prevention programs, many cases of colorectal cancer (CRC) are diagnosed when they have already metastasized. Herein, chemotherapy is required, and combination of 5-fluorouracil, irinotecan, and leucovorin (FOLFIRI) is one of the first-line treatments chosen. However, it is so toxic that compromises patient outcomes. Thus, with the aim of improving FOLFIRI pharmacokinetics while reducing its side effects, the three compounds that make it up were simultaneously absorbed in this work into polydopamine nanoparticles (PDA NPs), also loaded with an antibody to target CRC cells overexpressing the epithermal growth factor receptor (EGFR). All adsorptions, which were successfully executed without toxic solvents, were electrostatic in nature according to the calorimetry results obtained. Otherwise, based on the experiments done, 5-flurouracil, irinotecan, and leucovorin release from PDA NPs followed a burst-like pattern, which was possibly mediated by Fickian diffusion mechanisms. Finally, the assays performed with two EGFR-overexpressing CRC cell lines showed that the uptake of the nanosystem was rapid, and that its therapeutic effect was very significant. It managed to greatly reduce the viability of these cells to 22–30% after 72 h of incubation. Furthermore, when tumor spheroids were developed and treated with PDA NPs loaded with FOLFIRI and the anti-EGFR antibody (FOLFIRI-CTX@PDA NPs), these demonstrated to continue to have very marked therapeutic activity. In addition, FOLFIRI-CTX@PDA NPs affected to a lesser extent the survival rate of stromal cells, with which viability experiments were also done. Therefore, the novel developed PDA nanocarrier could be a promising strategy to enhance metastatic CRC therapy hereafter.